IPTEKS SISTEM PENGENDALIAN INTERNAL TERHADAP PELAYANAN PUBLIK DI KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN KELAS I BITUNG - Fajriansyah, Yudi; Alexander, Stanly W. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Every country, the organization of public services is an obligation for the government to meet the needs and rights of every citizen in the form of goods, services and administration. To realize a good public service then takes the name of the internal control system, wherein the internal control function to control every activity that occurs in the organization in order to create public services effectively and efficiently. As a public sector organization, Kantor Kesyahbandaran dan Otoritas Pelabuhan (KSOP) Kelas I Bitung has given good public services to the people especially those in need of service in the field of shipping and ports because based on the evaluation of the implementation of the internal control system it is quite effective even though there are some obstacles in the provision of public services but this can be overcome if they further increase their internal controlKeywords: public services, internal control system, public sector organization, KSOP, evaluation